Perceptual organization of speech signals by children with and without dyslexia - Nittrouer, Susan (2013)
Developmental dyslexia is a condition in which children encounter difficulty learning to read in spite of adequate instruction. Although considerable effort has been expended trying to identify the source of the problem, no single solution has been agreed upon. The current study explored a new hypothesis, that developmental dyslexia may be due to faulty perceptual organization of linguistically relevant sensory input. To test that idea, sentence-length speech signals were processed to create either sine-wave or noise-vocoded analogs. Seventy children between 8 and 11 years of age, with and without dyslexia participated. Children with dyslexia were selected to have phonological awareness deficits, although those without such deficits were retained in the study. The processed sentences were presented for recognition, and measures of reading, phonological awareness, and expressive vocabulary were collected. Results showed that children with dyslexia, regardless of phonological subtype, had poorer recognition scores than children without dyslexia for both kinds of degraded sentences. Older children with dyslexia recognized the sine-wave sentences better than younger children with dyslexia, but no such effect of age was found for the vocoded materials. Recognition scores were used as predictor variables in regression analyses with reading, phonological awareness, and vocabulary measures used as dependent variables. Scores for both sorts of sentence materials were strong predictors of performance on all three dependent measures when all children were included, but only performance for the sine-wave materials explained significant proportions of variance when only children with dyslexia were included. Finally, matching young, typical readers with older children with dyslexia on reading abilities did not mitigate the group difference in recognition of vocoded sentences. Conclusions were that children with dyslexia have difficulty organizing linguistically relevant sensory input, but learn to do so for the structure preserved by sine-wave signals before they do so for other sorts of signal structure. These perceptual organization deficits could account for difficulties acquiring refined linguistic representations, including those of a phonological nature, although ramifications are different across affected children.